Simulation of Migration Law of Organic Pollutants in Circulating Wells - Xiaojie Li; Jianwei Zhang; Zhuojing Yang (Advances in Civil Engineering)
Groundwater resources are one of the most important freshwater resources for human beings. The protection of groundwater resources is an important measure for human survival. Therefore, it is extremely important to discuss the treatment of pollutants in groundwater. The purpose of this paper is to simulate and analyze the migration law of organic pollutants using the experimental circulating well. In the analysis, this paper uses the gas-liquid-solid three-state model to simulate the pollutants for organic pollutants. It independently analyzes pollutants in different states. For the movement law, this paper not only simulates the vertical transition circulation well in the laboratory but also simulates the transport law of pollutants in the well. The experimental results show that in the laboratory environment, the simulated value of the circulation well designed in this paper is not far from the actual value, and the accuracy rate is more than 90%. And according to the movement law of organic pollutants, it is found that the variable flow rate and the dispersion, porosity, and thickness of the skin have a great influence on the migration of pollutants.